An Ecological and Miniaturized Biological Method for the Analysis of Daptomycin Potency. (17th August 2020) - Richardi, Jessica Freitas; Kogawa, Ana Carolina; Belavenuto, Eliane Gandolpho Tótoli; Chorilli, Marlus; Salgado, Hérida Regina Nunes
Abstract: Background: Physicochemical and microbiological methods are found in the literature for the analysis of daptomycin, an antimicrobial. Objective: This paper brings a miniaturized turbidimetric microbiological method for analysis of daptomycin in lyophilized powder. Methods: The method was performed using 96-well microplates, 4-h incubation, 2, 4 and 8 μg/mL, 7% Staphylococcus aureus ATCC 6538 IAL 2082, and BHI broth. Results: Linearity was proven by obtaining analytical curves with a correlation coefficient greater than 0.99 and statistical evaluation by ANOVA. The method was also selective, since the standard and sample analytical curves were parallel, proving that the excipient does not interfere with daptomycin analysis. Intraday, interday and inter-analyst precision presented RSDs of 2, 2.27, and 1.08%, respectively. Accuracy was assessed by the recovery test, where known quantities of standard solution are added to the sample and an average recovery value of 100.73% (RSD = 0.71%) was obtained. The present method was robust when minor changes were made in the parameters of used antimicrobial volume, inoculum volume and incubation time. Conclusions: This work is an innovative and ecological proposal and has advantages such as (i) less waste generation, (ii) miniaturized quantities of sample, culture media and inoculum, (iii) no need to use formaldehyde as in the traditional turbidimetric method, (iv) lower volume of glassware used and (v) shorter incubation time compared to other methods as agar diffusion requiring approximately 24 h. Highlights: This work is focuses on a current, innovative and sustainable theme for pharmaceutical analysis around the world.